An Economic Analysis of Attendance Demand for One Day International Cricket1. Issue 296 (11th December 2015) - Sacheti, Abhinav; Paton, David; Gregory‐Smith, Ian
Abstract : The future of One Day International (ODI) cricket has come under scrutiny following increasing competition from other formats of cricket. We identify trends in attendance demand by examining over 540 ODI matches played in Australia and England between 1981 and 2015. We use fixed effects and Tobit random effects models to isolate key determinants of attendance demand for ODI cricket and, in particular, the impact of uncertainty of outcome. We find that team strength has little independent effect on ODI attendances, but the uncertainty of the match outcome, as measured by the relative strengths of the teams over a long period of time, increases demand for ODI matches in England. Further, organising the ODI as a day/night (floodlit) game has a large positive impact on attendance in Australia.